Evaluation of oxidized rendered protein meals in pet foods - Gray, Morgan (Kansas State University, 2015)
Rendered protein meal is an important source of dietary protein and fat in pet food. However, fats in rendered meals can oxidize rapidly if not protected. The most common measurement of oxidation is the peroxide value (PV), but the analysis is highly variable. Additionally, the incorporation of oxidized protein further shortens its shelf life. Therefore, our objectives were to evaluate methods to measure fat quality in rendered protein meals and to determine the effect of increasingly oxidized protein meals on the shelf life of extruded pet foods. In Experiment 1, samples of five chicken byproduct meals (CBPM) from each of three locations and five beef meat and bone meals (BMBM) from each of two locations were analyzed for PV, anisidine value (AV), and thiobarbituric acid reactive substances (TBARS). The PV varied by method and location (P < 0.05). The alternative oxidation analytical methods, AV and TBARS, were not strongly correlated to PV (R² > 0.01). In Experiment 2, one metric ton of each unpreserved CBPM and unpreserved BMBM were collected and left unpreserved (U) or preserved with either ethoxyquin (E) or mixed tocopherols (T). These were held at ambient conditions (25°C, 51% RH) and monitored for PV and AV until values plateaued (41 and 63 days for CBPM and BMBM, respectively). Each “aged” meal was then incorporated into a model extruded cat food diet (~30% protein). Samples of kibble for each treatment were collected and stored at an elevated temperature and humidity (40°C, 70% RH) for 18 weeks and an ambient temperature and humidity (~22°C, 45% RH) for 12 months. The initial reduction (P < 0.05) in PV of the U (highly oxidized) BMBM and CBPM after processing suggests oxidation levels were diluted by food production. The oxidized meal led to a shorter shelf life (P < 0.05) in the finished food by PV analysis; but, sensory analysis by quick assessment did not completely corroborate these findings. These results suggest that PV doesn’t fully describe rendered protein meal stability or have a direct impact on shelf life for consumers; but may have a negative impact on pets due to oxidized lipid consumption.
Keywords: Rendered protein meal; Pet food; Extrusion; Shelf life; Oxidation; Peroxide value; Animal Sciences (0475); Food Science (0359)